Wells' Syndrome Successfully Treated with Colchicine - Puzas, Álvaro Iglesias (Case Rep Dermatol, 2017)
Eosinophilic cellulitis is an uncommon, inflammatory and chronic disorder of unknown etiology. Corticosteroids are currently considered as the first-line treatment but they are not without significant disadvantages such as contraindications in steroid-resistant cases and patients with frequent recurrences. We report a patient suffering from Wells' syndrome with a 24-year history of symptomatic and generalized skin lesions. After consultation in our department, treatment with colchicine 1 mg/day was prescribed resulting in large clinical improvement. No side effects have been recorded. To our knowledge, this is an original disease approach. Although small, our clinical experience supports the inclusion of colchicine in the drug armamentarium when treating patients suffering from Wells' syndrome. Indeed, its excellent safety profile makes it very attractive for patients with frequent recurrent episodes who need secure options for the medium- and long-term disease control.